5(-6)+14x=22x-(-6)

Simple and best practice solution for 5(-6)+14x=22x-(-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-6)+14x=22x-(-6) equation:


Simplifying
5(-6) + 14x = 22x + -1(-6)

Multiply 5 * -6
-30 + 14x = 22x + -1(-6)

Multiply -1 * -6
-30 + 14x = 22x + 6

Reorder the terms:
-30 + 14x = 6 + 22x

Solving
-30 + 14x = 6 + 22x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-22x' to each side of the equation.
-30 + 14x + -22x = 6 + 22x + -22x

Combine like terms: 14x + -22x = -8x
-30 + -8x = 6 + 22x + -22x

Combine like terms: 22x + -22x = 0
-30 + -8x = 6 + 0
-30 + -8x = 6

Add '30' to each side of the equation.
-30 + 30 + -8x = 6 + 30

Combine like terms: -30 + 30 = 0
0 + -8x = 6 + 30
-8x = 6 + 30

Combine like terms: 6 + 30 = 36
-8x = 36

Divide each side by '-8'.
x = -4.5

Simplifying
x = -4.5

See similar equations:

| 5y=2y+g | | 8x(x+7)=5x+35 | | 30-4-7=m | | mg=5 | | 3/10-3/5= | | Tan(55)*20=x | | 225-8y=17 | | -2(3x-4)=4x-10-x | | 1.5x(x-2)+9=1.5x+6 | | 7x^3-x^2+14x+7xy=0 | | 3.4x=-0.238 | | lny=ln(9x)+c | | .3333x=8 | | 4x-9-2x=-4 | | 1/(2x-4)=7/3 | | Tan(55)2*20=x | | log(8x-9)-log(x-1)=1 | | 5+4x=2+8x | | 1/(2x-4)=31/24 | | -5.4-7.8x=-78.4 | | ln(x)=ln(2) | | 2/3x-9=1/2x-8 | | 10t-4=-3 | | 31=7k-4 | | -4(2x+3)=2(3x-2) | | 2.5x+46.8=14.7-8.2x | | 2(4w+1)-2w=5w-1 | | 100/×=-4 | | -10x=8x-7 | | 3x-59=34 | | 1/2x-400=5000 | | 2/7=35/h |

Equations solver categories